Effect of exercise intervention on smoking cessation: a meta-analysis - Zhou, Yuehui; Feng, Wenxia; Guo, Yugang; Wu, Juhua (Frontiers in Physiology, 2023)
Background: Exercise has emerged as an effective approach to promote individual health and has shown potential in aiding smoking cessation. However, the specific benefits of exercise in smoking cessation remain unclear, and conflicting findings across studies may be attributed to variations in study populations and intervention characteristics. This study aims to conduct a meta-analysis to evaluate the impact of exercise interventions on tobacco dependence in smokers and assess the effectiveness of exercise in facilitating smoking cessation.Methods: A comprehensive search was performed in databases including PubMed, Web of Science, Embase, The Cochrane Library, and Scopus to identify relevant randomized controlled trials published before October 30, 2022December 12, 2021. The Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines were followed during the review process. The quality of evidence (QoE) was assessed with GRADE (grading of recommendations, assessment, development and evaluations) methodology.Results: Acute exercise was found to significantly reduce smoking cravings [MD = -1.84, 95% CI (-2.92, -0.76), P < 0.001; SMD = -1.64, 95% CI (-2.22, -1.05), P < 0.001] and alleviate most withdrawal symptoms in smokers. However, there was no significant difference in the smoking cessation rate between the exercise group and the control group (P > 0.05). Exercise was associated with increased positive mood [SMD = 0.36, 95% CI (0.14, 0.58), P = 0.001] and reduced negative mood in smokers [SMD = -0.26, 95% CI (-0.39, -0.12), P < 0.001].: Acute exercise interventions effectively reduce cravings and withdrawal symptoms in smokers. However, long-term exercise interventions do not significantly improve the smoking cessation rate. Exercise can help reduce negative mood and enhance positive mood in smokers. Smokers with high levels of tobacco dependence may derive less benefit from exercise. Factors such as literature quality, exercise intervention characteristics, and exercise adherence may influence the effectiveness of interventions.